Terapi Tasawuf untuk Problem Spiritual Masyarakat Modern - Mia Tyas Diti Savitri (Gunung Djati Conference Series, 2023)
This study aims to discuss sufism as a therapy for the spiritual problems of modern society. This study uses a qualitative approach by applying a descriptive-analytical method. The results and discussion in this study show that sufism can be a remedy for societal anxiety in this modern era by bringing enlightenment to inner peace and peace of life. The understanding of sufism teaches that spirituality is an inherent part, even the essence of sufism itself. This study concludes that technological developments and advances have positive impacts but also negative impacts that can be overcome by sufism as a modern therapy. This study recommends to various parties to instill the value of Sufism with a method that can be accepted by all levels of society in this modern era of onslaught.